The eye that never sleeps : how Detective Pinkerton saved President Lincoln - Moss, Marissa (Abrams Books for Young Readers, 2018)
Offers an illustrated look at the life and career of Allan Pinkerton, with a special focus on the specifics of how he successfully thwarted a plot to assassinate Abraham Lincoln in Baltimore before he was sworn in as president.